Modelling of partial discharge analysis system using wavelet transform denoising technique - Siti Huzaimah Kamal Hamadi (School of Electrical System Engineering, 2018)
The objectives for this project are; to develop partial discharge analysis system using Discrete Wavelet Transform (DWT) denoising technique; to evaluate the performance of partial discharge analysis system based on Mean Square Error (MSE); to evaluate the performance of partial discharge analysis system based on Signal-to-Noise Ratio (SNR).